Nontuberculous Mycobacteria: Ecology and Impact on Animal and Human Health - Pavlik, Ivo; Ulmann, Vit; Falkinham, Joseph O (Microorganisms, 2022)
Nontuberculous mycobacteria (NTM) represent an important group of environmentally saprophytic and potentially pathogenic bacteria that can cause serious mycobacterioses in humans and animals. The sources of infections often remain undetected except for soil- or water-borne, water-washed, water-based, or water-related infections caused by groups of the Mycobacterium (M.) avium complex; M. fortuitum; and other NTM species, including M. marinum infection, known as fish tank granuloma, and M. ulcerans infection, which is described as a Buruli ulcer. NTM could be considered as water-borne, air-borne, and soil-borne pathogens (sapronoses). A lot of clinically relevant NTM species could be considered due to the enormity of published data on permanent, periodic, transient, and incidental sapronoses. Interest is currently increasing in mycobacterioses diagnosed in humans and husbandry animals (esp. pigs) caused by NTM species present in peat bogs, potting soil, garden peat, bat and bird guano, and other matrices used as garden fertilizers. NTM are present in dust particles and in water aerosols, which represent certain factors during aerogenous infection in immunosuppressed host organisms during hospitalization, speleotherapy, and leisure activities. For this Special Issue, a collection of articles providing a current view of the research on NTM-including the clinical relevance, therapy, prevention of mycobacterioses, epidemiology, and ecology-are addressed.
Keywords: potentially pathogenic mycobacteria; saprophytic mycobacteria; biofilm formation; environmental saprophytic mycobacteria; aerosolization; hydrophobic; surface microlayer; natural and human-engineered water systems; geophagia; estuarine; saprozoic mycobacteria